Influence of COVAW Capacity Building on Gender-Based Violence Program Performance in Narok County, Kenya - Indasi, Noel Mmboga (American Journal of Strategic Studies, 2024)
Purpose: The study explores the influence of employee capacity building on the performance of gender-based violence (GBV) programs in Narok County, Kenya. The specific objectives include examining the effect of leadership style, the impact of community empowerment on program effectiveness, the role of resource allocation, and the influence of organizational innovation on program outcomes. Methodology: Utilizing a descriptive survey design grounded in modernization theory and performance and human capital theory, the research targets full-time staff from ten GBV programs operated by COVAW. A sample of 92 respondents is collected through convenience and stratified sampling techniques, incorporating both community participants and program personnel. Data collection employs interview schedules and semi-structured questionnaires, with quantitative data analyzed using SPSS software and qualitative data thematically analyzed. Findings: Findings reveal a prevailing democratic leadership style that fosters collaboration; however, community empowerment faces challenges due to inadequate integration and mobilization. The study concludes that there is a significant interconnectedness among leadership, community engagement, resource management, and organizational adaptability in enhancing GBV program performance. Unique Contribution to Theory, Policy and Practice: Recommendations include adopting diverse leadership styles, strengthening community engagement, and optimizing resource management practices to ensure the sustainability and impact of GBV initiatives.